Análise de parâmetros relevantes em culturas de vigilância epidemiológica de pacientes internados no centro de tratamento intensivo e colonizados por microrganismos multirresistentes - Alessandro Pacheco Silveira Martins (2022)
Determining the composition and concentration of microorganisms in health care services are extremely important components for health management. Based on this information, strategies can be developed to maintain a biologically safe hospital environment by eliminating contact and transmission foci and, thus, preventing Health Care-Related Infections (HAI). In the Intensive Care Center (ICU) infection and/or colonization by multidrug-resistant microorganisms (MR) stand out, so it is important to routinely use tools that allow the monitoring of patients with MR and utilities that predict the development of HAI. In this context, this study aimed to evaluate the performance of epidemiological surveillance swabs in ICU patients in a large public hospital in BH/MG, as a predictor of the occurrence of HAI caused by MR in the period 2018-2020. For this purpose, medical records of patients admitted to the ICU submitted to epidemiological surveillance cultures and the factors correlated to the development of HAI were evaluated, characterizing it as a descriptive, retrospective and observational, non-interventional study. The analyzes showed MR colonization in 9.5% of the samples collected at the ICU, with a higher frequency of Gram negative bacteria, including A. baumannii, P. aeruginosa, K. pneumoniae and carbapenem-resistant Enterobacteriaceae. The study population showed a predominance of male patients, mean age of 59 years, graduated from the Medical Clinic, with an average of 22 days of hospitalization in the ICU, with septicemia being the main cause of hospitalization in the ICU. The most used antimicrobials were β-lactams and glycopeptides, and the same patient used more than one class of antimicrobials for treatment. Within the invasive parameters evaluated, it was demonstrated that there is a correlation between the occurrence of colonization and infection by MR, causing an increase in mortality rates. The performance of the epidemiological surveillance culture had a positive predictive value of 17% in predicting the emergence of an HAI, proving to be an ineffective predictor. However, the surveillance culture is extremely important to know the microbiological profile of the institution through the collection of swab from different sites to regulate and adopt actions and measures aimed at controlling and reducing HAI rates, as well as the emergence of MR, in order to create and maintain a biologically safe and effective environment for health care.